Case Study of Oriental Medicine Treatment with Acupotomy Therapy of the Peroneal Nerve Palsy through Ultrasound Case Report - Kim Sungha; Park Man-young; Lee Sangmi; Lee Sangkwan; Lim Jinyoung; Kim Sungchul (Korean Pharmacopuncture Institute, 2011)
Purpose: In order to estimate clinical effects of Oriental Medicine Treatment with acupotomy therapy of Peroneal nerve Palsy. Methods: From 10th June, 2010 to 19th June, 2010, 1 female patient diagnosed as Peroneal nerve Palsy(clinical diagnosed) was treated with general oriental medicine therapy (acupuncture, pharmacopuncture,moxibustion, cupping, physical therapy, herbal medication) and acupotomy. Results: The patient's left foot drop was remarkably improved. Conclusions: This study demonstrates that oriental medical treatment with acuputomy therapy has notable effect in improving symptoms of peroneal nerve palsy. as though we had not wide experience in this treatment, more research is needed.